Jupiter's Aurora Observed With HST During Juno Orbits 3 to 7. Issue 5 (1st May 2018) - Grodent, Denis; Bonfond, B.; Yao, Z.; Gérard, J.‐C.; Radioti, A.; Dumont, M.; Palmaerts, B.; Adriani, A.; Badman, S. V.; Bunce, E. J.; Clarke, J. T.; Connerney, J. E. P.; et al.
Abstract: A large set of observations of Jupiter's ultraviolet aurora was collected with the Hubble Space Telescope concurrently with the NASA‐Juno mission, during an eight‐month period, from 30 November 2016 to 18 July 2017. These Hubble observations cover Juno orbits 3 to 7 during which Juno in situ and remote sensing instruments, as well as other observatories, obtained a wealth of unprecedented information on Jupiter's magnetosphere and the connection with its auroral ionosphere. Jupiter's ultraviolet aurora is known to vary rapidly, with timescales ranging from seconds to one Jovian rotation. The main objective of the present study is to provide a simplified description of the global ultraviolet auroral morphology that can be used for comparison with other quantities, such as those obtained with Juno. This represents an entirely new approach from which logical connections between different morphologies may be inferred. For that purpose, we define three auroral subregions in which we evaluate the auroral emitted power as a function of time. In parallel, we define six auroral morphology families that allow us to quantify the variations of the spatial distribution of the auroral emission. These variations are associated with changes in the state of the Jovian magnetosphere, possibly influenced by Io and the Io plasma torus and by the conditions prevailing in the upstream interplanetary medium. This study shows that the auroral morphology evolved differently during the five ~2 week periods bracketing the times of Juno perijove (PJ03 to PJ07), suggesting that during these periods, the Jovian magnetosphere adopted various states. Key Points: The study presents the results of a large HST campaign observing Jupiter's UV aurora, concurrently with the in situ exploration of its magnetosphere with Juno The study provides an original analysis method based on the definition of six morphological families tentatively associated with Jupiter's magnetospheric state This HST data set provides crucial synergistic measurements and additional opportunities to augment the Juno mission science return